(untitled) (Texas Journal of Medical Science, 2025)
External genital endometriosis (EGE) is a chronic inflammatory condition characterized by the presence of endometrial-like tissue outside the uterus, leading to pain and infertility. Inflammatory cytokines are known to play a critical role in the pathogenesis of EGE. This study investigates the impact of surgical intervention on the modulation of inflammatory cytokine levels in women with EGE. Serum samples were collected from patients preoperatively and at various time points postoperatively to measure key inflammatory cytokines. Cytokine levels were quantified using enzyme-linked immunosorbent assays (ELISAs). The results indicate significant changes in the levels of specific inflammatory cytokines following surgery, suggesting a potential mechanism by which surgery alleviates symptoms and improves outcomes in EGE patients. These findings contribute to a better understanding of the immunological aspects of EGE and may inform future therapeutic strategies.